Gastropods in tidal of Bulo, Mandolang District, North Sulawesi - Azzahra Aulina; Ompi, Medy; Kaligis, Erly Yosef; Rumampuk, Natalie Detty C; Rimper, Joice Rinefi T.S.L; Gerung, Grevo S. (Jurnal Ilmiah Platax, 2024)
A tidal area is a part of the coast that is influenced by the rise and fall of the tides. The area is a dynamic area, which experiences exposure to the air when low tide comes, easily mixed with fresh water in the rainy season and inundation. Marine flora and fauna that live in the area can adapt to it. The purpose of this study was to identify gastropod species and the density of each species that were found attached to the hard substratum in the tidal area of Bulo, Mandolang District, North Sulawesi. Data were collected by line transect and squared methods. Gastropod samples obtained were treated by using 70% alcohol. The length of each species was measured before being identified at the species level. The results show 175 individuals consisting of 30 species from 14 families were recorded. Substrat of rock and dead coral were covered and dominated the intertidal bottom. The highest density of Gastropods in the tidal area of Bulo, Mandolang District, North Sulawesi was the species of Cellana radiata. The density of Cellana radiata was 3.8 ind./m², while for the other 20 species of gastropods, each species was 0.07 ind./m². Physical and biological factors that affected the presence and density of gastropod species are discussed. Keywords: Gastropods; Density; Tidal; Mollusc; Bulo Village. Abstrak Daerah pasang surut adalah salah satu daera di pesisir yang dipengaruhi oleh air pasang tinggi dan rendah. Daerah ini adalah sebagai daerah yang dinamamis, di mana adalah daerah yang terekspos dengan sinar matahari pada saat pasang rendah, mudah bercampur dengan air tawar di saat musium hujan, serta daerah yang mudah dijangkau oleh masyarakat pensisir. Biota yang hidup di daerah ini memiliki kemampuan beradaptasi dengan perubahan-perubahan lingkungan ini. Tujuan penelitian ini adalah mengidentifikasi jenis-jenis Gastropoda dan mengetahui kepadatan jenis-jenis Gastropoda, yang menempati substrat keras di daerah pasang surut Bulo Kecamatan Mandolang, Sulawesi Utara. Pengumpulan data adalah dengan menggunakan metode ‘line transect’ dan kuadrat. Sampel Gastropoda yang didapatkan diberi alkohol 70%, Panjang masing-masing spesies diukur sebelum diidentifikasi pada tingkat spesies. Hasil penelitian menunjukkan bahwa ada 175 individu yang terdiri dari 30 spesies dari 14 famili. Kepadatan tertinggi Gastropoda di daerah pasang surut Bulo Kecamatan Mandolang, Sulawesi Utara adalah Cellana radiata yang memiliki kepadatan 3.8 ind./m2, sedangkan 20 jenis Gastropoda lainnya memiliki kepadatan untuk setiap jenis, yaitu 0.07 ind./m2. Kata kunci: Gastropoda; Kepadatan; Pasang Surut; Moluska; Desa Bulo.